Technology Governance: Minding and Closing the Gaps in Africa - SOKFA FRANCIS JOHN (African Journal of Governance and Development, 2021)
Technological innovation is at the heart of human evolution and progress. It is a catalyst for human well-being and socio-economic development. The rapid advancement the world is currently witnessing in this regard also birth concerns and ambiguities around the tension between benefits of today’s innovations and technologies and their actual and potential harm or risks. This paper outlines some key challenges to the global governance of emerging technologies to maximise benefits while preventing harm. The paper also identified some gaps in technology governance in Africa, their implications, and some key issues that need to be considered in closing these gaps. It argues that African governments, the corporate sector, academic institutions and other stakeholders need to begin to engage the current state of innovations and technologies and their possible futures and implications for the continent more critically and innovatively. This will require approaches informed by current needs and future thinking, are in sync with global trends, and prioritise Africa’s interests and needs. The current decolonisation debates in Africa should specifically inform such approaches. That will address the emerging patterns of coloniality observed in the current technological landscape and prevent the future occurrence of such practices. Additionally, considering rural African populations and their importance to the continent’s sustainable development, approaches to technological governance should also aim to centralise rather than marginalise rural communities. The paper concludes by highlighting some key areas of future research, such as investigating ways to achieve inclusive, just and equitable technological governance.